Comprehensive comparative metabolome study of a large collection of Corsican bryophytes - Pannequin, Anaïs; Muselli, Alain; Marcourt, Laurence; Ferreira Queiroz, Emerson; Quiros-Guerrero, Luis-Manuel; Asakawa, Yoshinori; Dounoue-Kubo, Miwa; Wolfender, Jean-Luc (Frontiers in Plant Science, 2025)
Bryophytes are non-vascular plants that appeared on Earth before vascular plants. More than 24,000 species are reported worldwide, and only a small proportion have been studied. However, part of their biosynthetic potential has been unveiled and more than 1,600 terpenoids have been detected and identified. The study of bryophytes faces challenges due to their small size, and sociology, making it difficult to collect large amounts of uncontaminated samples. Additionally, their chemical specificity and the scarcity of chemical data specific to this branch further complicate their study. Traditionally, research on bryophytes has focused only on specific species or classes of compounds. In contrast, our work proposes the first untargeted metabolite profiling investigation of a large collection of bryophytes (63 species) mainly issued from Corsican biodiversity. Metabolite profiling was performed by UHPLC-HRMS/MS and the data was extensively annotated using computational tools and molecular networking. This allowed us to describe in detail the chemical space covered by our collection and to establish comparisons between all the moss and liverwort species available. To validate some of the structural annotations, 3 liverworts (Frullania tamarisci, Pellia epiphylla, Plagiochila porelloides) and 2 mosses (Antitrichia curtipendula and Dicranum scoparium), available in larger quantities were fractionated using high-resolution semi-preparative HPLC, yielding 20 pure compounds. Five of them were newly discovered. This study highlights the main compositional differences between mosses and liverworts at the chemical class level. By analyzing given molecular network clusters, specific biosynthetic features or compounds that are characteristic of certain species are highlighted and discussed in detail.